The effect of shear rate on apparent viscosity for different pulp suspensions - Vaz, Álvaro (2010)
The goal of this work was to study the relationship between chemical pulps suspensions rheology and the operating variables of refining for three different paper fibres, namely Pinus sylvestris, Eucalyptus globulus and Betula verrucosa. The intention was the establishment of the best conditions for the refining of chemical pulps for paper production. In order to obtain that, the hydromechanics of the beating was analysed for the three pulps. So, the normal and tangential forces were evaluated, the distance between rotor and stator was measured and the pulp apparent viscosity evolution during refining was calculated. The refining essays took place in a laboratory Valley refiner, and the studied variables were the charge on the roll, the rotor speed of rotation and the specific applied energy. A global relationship between the apparent viscosity and the shear rate was finally obtained.